Through thick and thin: young people's affective geographies in Brussels' public space - De Backer, M. (2018)
Young people's interaction with place is not only a cognitive process of identification but also an affective relation. There has been plenty of research on young people and/in public space but few of those studies have taken such an affective layer of analysis into account. In this paper we aim to shed some light on young people's affective geographies through the concept of ‘thick places’ as it was proposed by Edward Casey (2001), building upon ethnographic research undertaken between 2013 and 2016 in Brussels. We argue that such a concept is only useful if we consider thickness not only as a reference to ‘warm’, ‘authentic’ or ‘intimate’ places but also as a term that takes the ‘normative architecture’ of place into account. We embed this claim in a discussion of affects, atmospheres and Peter Sloterdijk's notion of nomotop.